Analysis of the influence of work solidarity and teamwork on employee performance satisfaction in regional public drinking water companies - Mutiafani, Yessabilla Aning; Hakim, Lukman (Institute of Computer Science (IOCS), 2025)
This study explores the impact of work cohesion and team collaboration on employee performance satisfaction at PDAM Tirta Makmur Sukoharjo. Utilizing a quantitative approach with an associative research design, the study examines the relationship between work cohesion, team collaboration, and employee performance satisfaction. Data was collected through a questionnaire, with responses measured using a Likert scale. The sampling technique employed was probability sampling, incorporating both random and purposive sampling methods. Data analysis was conducted using SmartPLS 3.0 software and multiple regression methods, with validity and reliability tests applied. The findings indicate that both work cohesion and team collaboration have a positive effect on employee performance satisfaction, with team collaboration exerting a more dominant influence. These results highlight the crucial role of a collaborative work environment in enhancing employee performance satisfaction. The study's limitations include its focus on a single company and a relatively small sample size. Future research is recommended to expand the scope and incorporate additional variables for a more in-depth understanding